Soyabean protein concentrate as parcial substitute of milk protein in milk replacers for calves - Alvarez, Júlio Cézar (1999)
Twenty four Holstein calves were alloted in a randomized block design, from 7 to 42 days of life. Four treatments, milk replacers used as the only feed source, were applied with several degrees of substitution of digestible protein from milk to soybean concentrate protein (SCP) (71% CP) as follows: (A) 100% of milk protein, (B) 80% of milk protein and 20% protein from SCP, (C) 60% of milk protein and 40% of protein from SCP; and (D) 40% of milk protein and 60% protein from SCP. Average daily weight gains and dry matter feed conversions were statistically different (p<0.01) in a linear regression behaviour: (A) 405g and 1.78; (B) 388g and 1.87; (C) 258g and 2.81 and (D) 228 and 3.43. Days with diarrea had no differences among treatments.